Unintended Consequences: How COVID-19 Provided a Unique Opportunity for Disabled Workers - Savino, David M. (Journal of Knowledge Management Practice, 2024)
COVID-19 has been such a challenge for everyone across society in all countries and every economy. It has been one of the most disruptive phenomena experienced by anyone in over a century. Because of COVID-19 the very nature of work changed significantly and therefore many obstacles arose that had to be handled as well as some opportunities. Most organizations were caught off guard and as expected clung very hard to established work procedures and protocols that had been previously established. The result created a conflict between accepted corporate cultures and the forces for change to adapt to COVID-19 and its implications. One such issue was the sudden reliance on working remotely and its effects on workers, especially those with disabilities. While this study is about working remotely and those with disabilities, it is important to note up front that regardless of the type of workers involved employer opposition to remote work exists to some extent for all workers and is not particularly directly at those with disabilities.